2000
DOI: 10.1302/0301-620x.82b1.9740
|View full text |Cite
|
Sign up to set email alerts
|

Knee instability after injury to the anterior cruciate ligament

Abstract: We have measured anterior and posterior displacement in 563 normal knees and 487 knees with chronic deficiency of the anterior cruciate ligament (ACL). We performed stress radiography using a simple apparatus which maintained the knee at 20 degrees of flexion while a 9 kg load was applied. There was no significant difference in posterior translation dependent on the condition of the ACL. Measurement of anterior translation in the medial compartment proved to be more reliable than in the lateral compartment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 0 publications
1
35
1
Order By: Relevance
“…Only two studies in this review reported results for comparison of measurement techniques using different landmarks and reference points on stress radiographs [28,30]. Although we recognize that the choice of landmarks may influence the accuracy and reliability of measurements in stress radiography, this was beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Only two studies in this review reported results for comparison of measurement techniques using different landmarks and reference points on stress radiographs [28,30]. Although we recognize that the choice of landmarks may influence the accuracy and reliability of measurements in stress radiography, this was beyond the scope of the present review.…”
Section: Discussionmentioning
confidence: 91%
“…No diagnostic accuracy data were reported for diagnosis of isolated varus knee injuries on stress radiography. Overall, excellent intrarater and interrater ICCs were reported for the diagnosis of ACL [28,30], PCL [28,42], varus [12,26], and valgus [25] injuries on stress radiography. However, only six studies included analysis of intrarater and interrater reliability [12,25,26,28,30,42].…”
Section: Stress Radiography Diagnostic Accuracy and Reliabilitymentioning
confidence: 87%
See 3 more Smart Citations